Physical oceanography during RV POLARSTERN cruise PS137 at Lucky B site - Walter, Maren; Mette, Jonathan (PANGAEA, 2025)
This dataset contains CTD (conductivity, temperature, depth probe) data and additional parameters for stations conducted during the cruise PS137. Additionally it contains corresponding navigational data from the ships positioning system. The stations were executed in July 2023 to detect possible hydrothermal plumes at the Lucky B site where hydrothermal activity was suspected at approximately 81° latittude and -3° longitude. The data was measured with a CTD rosette system and processed to correct sensor uncertainties and remove outliers. The original sample frequency of 24 Hz was averaged to 1 Hz.
Keywords: Arctic Ocean; CTD; hydrothermal activity; Lucky B